2016
DOI: 10.1016/j.neurobiolaging.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

The neurotrophin receptor p75 mediates gp120-induced loss of synaptic spines in aging mice

Abstract: Human immunodeficiency virus 1 and its envelope protein gp120 reduce synaptodendritic complexity. However, the mechanisms contributing to this pathological feature are still not understood. The proneurotrophin brain-derived neurotrophic factor promotes synaptic simplification through the activation of the p75 neurotrophin receptor (p75NTR). Here, we have used gp120 transgenic (gp120tg) mice to investigate whether p75NTR has a role in gp120-mediated neurotoxicity. Old (~10 months) gp120tg mice exhibited an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 60 publications
4
41
2
Order By: Relevance
“…In this study, we show that the amygdala of gp120tg mice with an anxiety behavior undergoes dendritic spine remodeling. The increase in the density of spines in the amygdala observed in this study is in contrast with a reduction of dendritic spines that we have previously detected in the hippocampus of these animals (Bachis et al, submitted). However, such discrepancy is not unusual because it has been demonstrated that the hippocampus and amygdala respond differently to anxiety caused by chronic stress.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, we show that the amygdala of gp120tg mice with an anxiety behavior undergoes dendritic spine remodeling. The increase in the density of spines in the amygdala observed in this study is in contrast with a reduction of dendritic spines that we have previously detected in the hippocampus of these animals (Bachis et al, submitted). However, such discrepancy is not unusual because it has been demonstrated that the hippocampus and amygdala respond differently to anxiety caused by chronic stress.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, we were not surprised to discover that spinogenesis in the amygdala was associated with an increase in BDNF levels. However, our data seems to be at odds with earlier study showing that gp120 reduces BDNF expression in the hippocampus of gp120tg mice (Bachis et al, submitted). Moreover, gp120 evokes a loss of BDNF expression both in neurons in vitro (Bachis et al, 2012) as well as in the caudate nucleus in vivo (Nosheny et al, 2004).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…One of the hallmark neuropathological features most correlating with these cognitive deficits in HAND is synaptodendritic damage, particularly decreased synaptic and dendritic density (Ellis et al 2007; Masliah et al 1997). These neuropathological indices are also confirmed in rodent models of HAND by showing significant neuronal atrophy accompanied by disruption to neuronal function (Bachis et al 2016; D’Hooge et al 1999; Toggas et al 1994). However, the mechanisms by which HIV damages the CNS remain obfuscated considering that microglia but not neurons are infected.…”
Section: Introductionmentioning
confidence: 54%
“…It is widely recognized that gp120, through chemokine receptors, is a potent neurotoxin, promoting neuronal injury in vitro in the picomolar range (Bachis et al 2003; Lipton et al 1991; Meucci and Miller 1996). Moreover, mice genetically expressing gp120 (gp120tg) exhibit neuropathological features observed in HAND, such as retracted neuronal processes (Toggas et al 1994) and loss of dendritic spines (Bachis et al, 2016). …”
Section: Viral Proteinsmentioning
confidence: 99%